Transfer of optogenetic vectors into the brain of neonatal animals to study neuron functions during subsequent periods of development - D. A. Lanshakov; U. S. Drozd; T. A. Zapara; N. N. Dygalo (Вавиловский журнал генетики и селекции)
Optogenetics, that is, the control of cell activity using light-sensitive ion channels opsins with light of a specific wavelength, is increasingly being used to study activities and functions of neurons. Expression of opsins in the cell membrane, followed by the acquisition by the cell of the sensitivity to light is achieved by means of viral vectors, often created on the basis of lentiviral or adeno-associated (AAV) viruses bearing the nucleotide sequence encoding the photo-channel proteins. Inclusion of the cell-specific promoter of interest into the transgene-expression cassette allows opsin to be produced only in the target cells. The aim of this work was to briefly describe the optogenetic method, as well as to analyze the possibility to use administration of viral vectors into the brain of neonatal animals to study the function of neurons in vivo during subsequent periods of development. In this analysis, 3-day-old rat pups received intracerebroventricular injections of optovector (pAAV-CAMKIIa-ChR2h134-YFP), coding for a photo channel, which activates neurons, and the yellow fluorescent marker protein under the CAMKIIa promoter specific for glutamatergic neurons under cold anesthesia. The peak expression of the transferred gene is usually achieved at week 3–5 after the transfer of the vector, which is what was also observed in our experiments. Stimulation of the hippocampal neurons with blue light in the 20-day-old animals, to which opto-vector was transferred at the 3rd day of life, increased the discharge activity of these neurons. This light stimulation increased expression of the recognized marker of neuronal activation protein c-Fos in these photosensitive cells too. The same experiments with older animals, 60 days after the neonatal opto-channel gene transfer, revealed no noticeable expression of this channel or photoactivation of target neurons of the hippocampus. Thus, neonatal administration of a viral vector carrying an opto-channel gene is suitable for the study of brain neurons in rats of juvenile age, and requires additional control for gene expression during subsequent periods of development.